Overview of Knowledge of Using PPE to Support Safety of Workers at CV. Duta Makmur Abadi - Ulfatun, Ulfatun Nadiyah Putri; Sahri, Moch; Wardana, Juwono; Raja’I, Juwono Muh Yasir (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Therefore, socialization aims to reduce the number of work accidents and work-related diseases in CV. Duta Makmur Abadi is engaged in making AC grille molds, by providing education to workers to pay more attention to health and safety when working, especially in the use of PPE. The methods applied in this socialization activity are conducting field observations and identifying dangerous factors in each production process, interviews through direct question and answer with workers, literature studies, and education in the form of posters with the theme "Cultivate Working Using Appropriate PPE". The result of this activity is that the workers already know enough about what PPE is, but they don't really care about the implementation related to PPE with an average score of 70. After being given a post test to determine the increase in ability, the score increased by 11.6, namely getting a score. an average of 81.6 for the Post test score. The author hopes that after providing education regarding the importance of PPE, workers can cultivate it and always use it during the production process. This is done with the aim of reducing the number of work accidents and ensuring that workers avoid the risk of work accidents.